2020
DOI: 10.21203/rs.3.rs-18079/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Utility of Ferritin, Procalcitonin, and C-reactive Protein in Severe Patients with 2019 Novel Coronavirus Disease

Abstract: Objectives It is of clinical significance to evaluate the disease severity and investigate possible biomarkers of 2019 Novel coronavirus disease (COVID-19). In this study, we aim to describe the clinical characteristics of infection makers in severe and very severe patients with COVID-19. Methods This is a single center, observational analysis. We enrolled 48 in-hospital severe patients with COVID-19 admitted to the West District of Union Hospital of Tongji Medical College and analyzed infection biomarkers in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
39
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 10 publications
8
39
0
2
Order By: Relevance
“…In one study with 20 COVID-19 patients, it was found that individuals with severe and very severe COVID-19 exhibited increased serum ferritin level, being serum ferritin in the very severe COVID-19 group significantly higher than in the severe 7 . In agreement with this, another study revealed that in patients who died by COVID-19, ferritin levels were high upon hospital admission and throughout the hospital stay.…”
Section: To the Editormentioning
confidence: 98%
“…In one study with 20 COVID-19 patients, it was found that individuals with severe and very severe COVID-19 exhibited increased serum ferritin level, being serum ferritin in the very severe COVID-19 group significantly higher than in the severe 7 . In agreement with this, another study revealed that in patients who died by COVID-19, ferritin levels were high upon hospital admission and throughout the hospital stay.…”
Section: To the Editormentioning
confidence: 98%
“…The D-dimer which is a marker of coagulation status was also elevated in the diabetic group compared to the nondiabetic group (50.5 vs. 33.3%). The levels of these inflammatory markers have been correlated with the severity of COVID-19 infection [68].…”
Section: Outcome Studies Of Type 2 Diabetic and Nondiabetic Populatiomentioning
confidence: 99%
“…Another meta-analysis performed by Shi et al [34] showed that elevated levels of CK-MB were associated with the severity of COVID-19 in patients. Furthermore, another study found that the serum levels of ferritin were markedly increased in patients with very severe COVID-19 compared with patients with severe COVID-19 [35]. Ferritin is particularly relevant as it is a mediator of immune dysregulation; it has been proposed that under extreme hyperferritinaemia, ferritin exerts direct immune-suppressive and pro-in ammatory effects, contributing to the cytokine storm observed in patients with COVID-19 [36].…”
Section: Resultsmentioning
confidence: 99%